2008
DOI: 10.1590/s0034-72992008000600016
|View full text |Cite
|
Sign up to set email alerts
|

Treinamento auditivo formal em idosos usuários de próteses auditivas

Abstract: A implantação de programas de reabilitação para o deficiente auditivo idoso é de grande importância. OBJETIVO: Verificar a eficácia de um programa de treinamento auditivo formal em idosos que receberam próteses auditivas há no mínimo três meses, por meio de testes de reconhecimento de fala e questionário de auto-avaliação. MÉTODO: Estudo de coorte contemporânea longitudinal. Foram selecionados 13 idosos usuários de próteses auditivas intra-aurais em adaptação binaural, de ambos os sexos, com idade média de 65,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…8 In contrast, the scores on the other tests (DPT, FPT and SSI) were not within the range of normality on the pre-training evaluation and statistically significant improvements on all three tests were found following auditory training, with the participants achieving normal quantitative results for the age group. [13][14][15]19,21,22,24 These findings demonstrate the effectiveness of auditory training. Previous studies report the stability of auditory processing behavior tests.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…8 In contrast, the scores on the other tests (DPT, FPT and SSI) were not within the range of normality on the pre-training evaluation and statistically significant improvements on all three tests were found following auditory training, with the participants achieving normal quantitative results for the age group. [13][14][15]19,21,22,24 These findings demonstrate the effectiveness of auditory training. Previous studies report the stability of auditory processing behavior tests.…”
Section: Resultsmentioning
confidence: 89%
“…Previous studies report the stability of auditory processing behavior tests. 11,21,24,25 Questions remain regarding who patients will use the skills learned in formal auditory training in activities of daily living and whether such skills will be maintained in the long term. However, studies have demonstrated that the demands of the environment itself lead to the maintenance of learned listening skills.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the mean performance on the SSW, SSI-ICM (-10) and DPT tests went from abnormal to normal, demonstrating the adequacy of hearing skills for temporal ordination and figure-background for verbal sounds (words). Previous studies have found improvements on all of these behavior tests following auditory training in different populations, such as individuals with APD, adult and elderly hearing aid wearers and victims of head trauma ( 25 29 ).…”
Section: Discussionmentioning
confidence: 95%
“…In this context, studies (20,21) which aimed to verify the efficiency of auditory training with elderly people wearing hearing aids concluded that the training, associated with the use of hearing aids, improves the performance of speech recognition skills and reduces the restricted participation of this population.…”
Section: Discussionmentioning
confidence: 99%